2013
DOI: 10.1038/srep02343
|View full text |Cite
|
Sign up to set email alerts
|

A ground-like surface facilitates visual search in chimpanzees (Pan troglodytes)

Abstract: Ground surfaces play an important role in terrestrial species' locomotion and ability to manipulate objects. In humans, ground surfaces have been found to offer significant advantages in distance perception and visual-search tasks (“ground dominance”). The present study used a comparative perspective to investigate the ground-dominance effect in chimpanzees, a species that spends time both on the ground and in trees. During the experiments chimpanzees and humans engaged in a search for a cube on a computer scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…Thus, our finding of a more veridical space perception on the ground adds to those of previous studies that found the visual system has a preference to efficiently process ground over ceiling surfaces (Bian et al, 2005; 2006, 2011; Imura & Tomonaga, 2013; Kavšek & Granrud, 2013; McCarley& He, 2000; McCarley& He, 2001; Morita & Kumada, 2003). …”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Thus, our finding of a more veridical space perception on the ground adds to those of previous studies that found the visual system has a preference to efficiently process ground over ceiling surfaces (Bian et al, 2005; 2006, 2011; Imura & Tomonaga, 2013; Kavšek & Granrud, 2013; McCarley& He, 2000; McCarley& He, 2001; Morita & Kumada, 2003). …”
Section: Resultssupporting
confidence: 86%
“…The important difference between the ground and ceiling reference frames is that the perceptual process underlying the ground surface representation is more efficient and reliable than the process underlying the ceiling surface representation. Indeed, previous studies have found that the visual system has a preference for the ground surface over the ceiling surface (Bian & Andersen, 2011; Bian et al, 2005, 2006; Imura & Tomonaga, 2013; Kavšek & Granrud, 2013; McCarley & He, 2000, 2001; Morita & Kumada, 2003). For example, when searching for an odd target in a 3D visual search display, the search reaction time was faster if the search elements were seen as belonging to a large implicit common plane than when the elements were seen as belonging to different planes (McCarley & He, 2000, 2001).…”
mentioning
confidence: 99%
“…The ground dominance effect refers to the phenomenon where observers show a preferred response according to the optical contact information provided by the ground surface. The advantage of ground surface information can apparently be applied to egocentric direction perception, in addition to distance perception ( Bian et al, 2005 , 2006 ; Bian and Anderson, 2011 ), heading ( Rushton et al, 1999 ), vection ( Sato et al, 2007 ), change detection ( Bian and Anderson, 2010 ) and visual search ( McCarley and He, 2000 ; Imura and Tomonaga, 2013 ). In this experiment, participants should look at “far” visual information (i.e., the vanishing point) using central vision and “near” visual information using peripheral vision in both image conditions, because the fixation point, which they were instructed to gaze at, was located close to the vanishing point.…”
Section: Methodsmentioning
confidence: 99%
“…They were not food-deprived and were fed fruits, vegetables, and primate chow three times each day during the study. They had previously engaged in various kinds of computer-controlled perceptual and cognitive tasks, including those involving matching to sample 19 21 22 39 40 41 42 43 44 . As a result, all chimpanzee participants were already familiar with generalised identity-matching tasks at the beginning of the present experiments; thus, we did not need to conduct any acquisition training for this group.…”
Section: Methodsmentioning
confidence: 99%